ANALISA SENSITIVITAS DURASI HUJAN PADA PERHITUNGAN DEBIT BANJIR DAS TENGGANG DAN SRINGIN - Pujiastuti, Ratih; Risna, Nevy (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2022)
Design flood is one of the important aspects in the design of water structures. Calculation of the design flood is very dependent on the existing rain data in the watershed area. The amount of flood discharge is not only influenced by the value of rainfall but also depends on the duration and distribution of rainfall per unit of time.This study was conducted to determine duration of rainfall that produces the maximum flood discharge for Tenggang and Sringin River. Calculation of flood discharge for Tenggang and Sringin River was carried out using a rainfall distribution pattern (hyetograph) for rainfall durations of 2 hours, 3 hours, 4 hours and 5 hours with the distribution of rainfall distribution referring to hourly rain data at Maritime Station. Results of analysis show that different distributions are produce different flood discharge values. For Tenggang and Sringin rivers, the maximum flood discharge value is obtained at a rain duration of 2 hours.Keywords: flood discharge, rainfall duration, hyetograph